2022
DOI: 10.1089/chi.2021.0221
|View full text |Cite
|
Sign up to set email alerts
|

Managing Obesity in Young Children: A Multiple Methods Study Assessing Feasibility, Acceptability, and Implementation of a Multicomponent, Family-Based Intervention

Abstract: Background: We developed a multicomponent, family-based intervention for young children with obesity consisting of parent group sessions, home nursing visits, and multidisciplinary clinical encounters. Our objective was to assess intervention feasibility, acceptability, and implementation. Methods: From 2017 to 2020, we conducted a multiple methods study in the obesity management clinic at a tertiary children's hospital (Toronto, Canada). We included 1–6 year olds with … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

0
2
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
5

Relationship

0
5

Authors

Journals

citations
Cited by 6 publications
(2 citation statements)
references
References 52 publications
(47 reference statements)
0
2
0
Order By: Relevance
“…13 Early childhood is an appropriate time for obesity intervention, for various reasons, including early life obesity intervention has been associated with very important effects, early life behaviors and patterns (eg, low physical activity, short sleep duration, inadequate consumption controlled) correlates well with the development and persistence of obesity, and behavior and lifestyle modifications appear to be more successful when applied at younger ages and have the potential to be sustained into adulthood. 14 people (91.4%) and <UMP there were 5 people (8.6%). Based on the number of family members in the control group, there were 28 (51.9%) family members of 4 people and >4 of 26 people (48.1%).…”
Section: Resultsmentioning
confidence: 99%
“…13 Early childhood is an appropriate time for obesity intervention, for various reasons, including early life obesity intervention has been associated with very important effects, early life behaviors and patterns (eg, low physical activity, short sleep duration, inadequate consumption controlled) correlates well with the development and persistence of obesity, and behavior and lifestyle modifications appear to be more successful when applied at younger ages and have the potential to be sustained into adulthood. 14 people (91.4%) and <UMP there were 5 people (8.6%). Based on the number of family members in the control group, there were 28 (51.9%) family members of 4 people and >4 of 26 people (48.1%).…”
Section: Resultsmentioning
confidence: 99%
“…Moreover, the authors concluded that there was a high level of heterogeneity when it came to both the designs and reported results of the included trials [14]. Interestingly, Kinlin and colleagues recently proposed an assessment of the feasibility and acceptability of their STOMP-EY family-based intervention, in which home visits from public health nurses were performed in addition to the parent-only group sessions [15]. According to their results, such family-based programs that include home visits face several barriers, such as the lack of relative priority and perceived patient need, lack of tailoring to individual patient needs, a poor parental motivation to engage in group sessions, and the challenges related to the scheduling and delivery of group sessions [15].…”
Section: Introductionmentioning
confidence: 99%